2019
DOI: 10.1136/bjophthalmol-2018-312933
|View full text |Cite
|
Sign up to set email alerts
|

Areal summed corneal power shift is an important determinant for axial length elongation in myopic children treated with overnight orthokeratology

Abstract: BackgroundThe myopia control effect of orthokeratology (OK) varies among individuals. The variation might relate to the proposed ‘areal summation effect’ of lens-induced visual signals. The current study evaluated the areal summed corneal power shift (ASCPS) in myopic children treated with OK lenses and assessed whether the ASCPS achieved at early post-OK visit can predict the lens long-term effect on the axial length (AL) elongation.MethodsStudy participants were 130 myopic children treated with OK lenses (ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 24 publications
5
37
1
Order By: Relevance
“…AL elongations of the OK and MFCL groups, 0.19 mm and 0.27 mm respectively, were consistent with the previous study (Paune et al, 2015). Our results suggest that the spatial distribution of the RCRPS, rather than the total amount (Zhong et al, 2015;Hu et al, 2019), is critical in slowing myopia progression. First, AL elongation was not related to the peak values, and the significantly greater peak values in MFCL subjects did not lead to smaller AL elongations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…AL elongations of the OK and MFCL groups, 0.19 mm and 0.27 mm respectively, were consistent with the previous study (Paune et al, 2015). Our results suggest that the spatial distribution of the RCRPS, rather than the total amount (Zhong et al, 2015;Hu et al, 2019), is critical in slowing myopia progression. First, AL elongation was not related to the peak values, and the significantly greater peak values in MFCL subjects did not lead to smaller AL elongations.…”
Section: Discussionsupporting
confidence: 91%
“…Subtracting the apex value from each point of the CRPS then derives the relative CRPS (RCRPS) that is related with the myopic shift in defocus on the peripheral retina ( Kang and Swarbrick, 2013 ). Some studies have suggested that RCRPS is strongly associated with AL elongation ( Zhong et al, 2014 , 2015 ; Lee et al, 2018 ; Hu et al, 2019 ). However, existing studies used only simple measures, such as the maximum value of either the whole map ( Lee et al, 2018 ) or along some axes ( Zhong et al, 2014 ), or the summed value within a certain area ( Zhong et al, 2015 ; Hu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 With a decentered treatment zone or a smaller treatment size, the reverse zone which has positive RCRPS moves closer to the apex. This could lead to a larger summed RCRPS within a 4 mm area, which agrees with the study by Yang et al 38 Given the same pupil size, TZD, and a smaller TZS, the summed RCRPS within the pupillary zone would be much greater in corneal power pro les, which would agree with the larger pupil size often associated with smaller axial growth. 18 We speculate that a smaller TZ and a higher decentered one will move the mid-peripheral ring inside the pupil if it is of the appropriate size, inducing higher optical changes that may be bene cial for myopia control in the subjects receiving orthokeratology treatment.…”
Section: The Potential Mechanismsupporting
confidence: 88%
“…[34][35][36] Cho et al 37 hypothesized that the greater the corneal reshaping effect, the greater peripheral myopic defocus, the higher the regulation e cacy in retarding myopia progression. Yang et al 38 suggested that areal summed corneal power shift (ASCPS) in a 4 mm area was a potential predictor of axial elongation in orthokeratology treatment. Wang et al 19 agreed that a maximum value of posttreatment corneal relative power (PCRP) resulted in a higher probability of effective axial elongation control.…”
Section: The Potential Mechanismmentioning
confidence: 99%